HUBUNGAN FAKTOR EKOLOGI DENGAN KEJADIAN MALARIA DI WILAYAH RAWAN MALARIA KECAMATAN SEKOTONG KABUPATEN LOMBOK BARAT - Iwan Desimal; Moch. Taufik Hidayatullah; Muhammad Fauzi; Endang Setiawaty (LPPM Institut Pendidikan Nusantara Global, 2023)
The report from the West Lombok Health Office stated that one of the malaria-prone areas in West Lombok Regency was Sekotong. Human activities such as illegal gold mining (PETI), abandoned ponds, construction of dams, and clearing of land for agriculture and pens have caused environmental changes that have led to the emergence of man-made mosquito breeding sites. The human environment consists of the natural environment, the built environment, and the social environment. The aim of this study was to analyze the relationship between ecological factors and the incidence of malaria in the Malaria Prone Area, Sekotong District, West Lombok Regency. Observational type research by means of ecological studies, research design using case control. The number of research samples was 76 people, namely 38 for the case group and 38 for the control group. The variables in this study were the independent variables, namely ecological factors such as the environment (tailing ponds, leftovers from gold mining without a permit, ditches, stables, gardens/bushes, hills and topography (altitude of the area). The dependent variable was the incidence of malaria. Data were collected using a questionnaire. Data were analyzed by descriptive analysis, contingency coefficient analysis. Based on bivariate analysis of ecological factors, it was obtained data that there was a relationship between the presence of ditches, cages, gardens/shrubs and altitude with the incidence of malaria in the Malaria Prone Area of Sekotong District, West Lombok Regency with sequential probability values ​​of 0.026, 0.026, 0.026 and 0.001 compared to significance level of 0.05. While the presence of tailings ponds, PETI excavation remains, and hills has no relationship with the incidence of malaria with p values ​​respectively 0.159, 0.068, 0.091.